The role of oxidative balance score in Cardiovascular-Kidney-Metabolic syndrome progression and mortality: insights from NHANES 1999–2020 - Xie, Diya; You, Fangqin; Yang, Lihang; Li, Cheng; Liu, Fengmin (Frontiers in Nutrition, 2025)
AimsCardiovascular-Kidney-Metabolic Syndrome (CKM) is a significant public health issue. This research explored the link between oxidative balance score (OBS) and the advancement of CKM, and assessed mortality risks across CKM stages in a U. S. cohort.MethodsData from 10 NHANES cycles (1999–2020) were analyzed, including 19,433 participants for primary analysis and 16,467 for survival analysis. Multinomial regression, Cox models, survival analysis and mediation analysis were employed to evaluate the relationships.ResultsThe OBS was robustly associated with CKM stages, with each increment reducing the odds of CKM stages 1–4 (OR 0.93–0.90, all p < 0.001). The highest OBS quartile (Q4) lowered advanced CKM odds (OR 0.77, 95% CI 0.59–0.99, p = 0.045). Higher OBS values were associated with a lower risk of all-cause mortality (HR 0.97, 95%CI 0.95–0.99, p < 0.001) and cardiovascular disease (CVD) mortality (HR 0.96, 95% CI 0.93–0.99, p = 0.012) in individuals with non-advanced chronic kidney disease (CKD), and with a lower risk of CVD mortality (HR 0.97, 95% CI 0.94–0.99, p = 0.014) in those with advanced CKD. Kaplan–Meier curves showed better survival in higher OBS quartiles, especially for non-advanced CKM. Inflammatory markers (Ln-WBC and Ln-SUA) mediated 26.08 and 15.17% of the total effect in advanced CKM.ConclusionImproving oxidative balance may mitigate CKM progression and mortality risks. Additional studies are required to clarify the mechanisms and public health significance of OBS in CKM.